QUATERNARY GEOLOGY OF THE CABINET, HERON AND SMEADS BENCH 7.5’ QUADRANGLES, WITH EMPHASIS ON GLACIAL LAKE MISSOULA SEDIMENTS - Welk, Emily (Digital Commons @ Montana Tech, 2019)
The primary scientific purpose of this project was to improve geologic knowledge of valley-fill units in the most downstream portion of the Clark Fork River valley in Montana. This was done to help understand the history of glacial Lake Missoula filling and draining cycles in the vicinity of the dam. The secondary purpose was to make a geologic map of the Cabinet, Heron and Smeads Bench 7.5-minute quadrangles and to resolve differences between detailed maps of Idaho (Lewis and others, 2008) and the old map of the Smeads bench, Heron and Cabinet quadrangles in Montana (Harrison and others, 1992; mapping was done 1977-87). Improving knowledge as to the timing and history of glacial Lake Missoula in this area was done by delineating the valley fill sediments and flood gravel deposits from newer alluvial gravels and glacial outwash. There are two large glaciolacustrine outcrops in the field area that were analyzed in detail. Stratigraphic sections show sections of repeating sequences of silt and clay couplets, that are unconformably separated by a thicker layer of fine grained, crossbedded sand and silt. Sands from both sections were sampled for Optically Stimulate Luminescence and Infrared Stimulated Luminescence burial age-analysis. The burial-age of our successful sample was 16.02 +/- 1.08ka, which is consistent with having been buried during the final stages of glacial Lake Missoula. The other sample was determined to be in error due to scatter in the signal. In the field area, massive gravel deposits were found in streamlined bars mid-channel along the banks of tributary channels and in areas protected from stream erosion such as meanders and topographical highs. The gravels were deposited by one or more massive floods that flowed through the valley when the ice dam broke. The gravel deposits are buttressed and mantled by glaciolacustrine sediments of glacial Lake Missoula and thus can be assumed to be the older of the two deposits. The preservation of the lake beds in the field area indicates that the final ...